Study on temperature field and residual stress in T welding joint of stainless steel - Nguyen Tien Duong, (Vietnam Journal of Science and Technology, 2025)
The stainless steel used more and more popularity in the construction and transport sector because they combine favorable aesthetic aspects, good mechanical properties and corrosion resistance. Hence, the stainless steel structures have a high long-life with low maintenance costs. The local heating and cooling during welding produce a non-uniform temperature distribution. Uneven shrinkage of the welded joint creates residual stress in welded structures. This paper studies the temperature field during welding and the residual stresses after welding in T welding joint of stainless steel by the imaginary force method and the finite element analysis. The thickness of SUS316L stainless steel plate in T-joint is 10 mm. Two welds on both sides of the T-joint are welded simultaneously by the MIG welding process. In this study, ESI SYSWELD finite element software is applied for thermo-mechanical analysis of stainless steel T welding joint. The residual stresses of this welding joint are calculated by the theory based on the imaginary force method. The results of temperature field and residual stresses in the T-joint are presented and discussed. The results of residual stresses by finite element method are compared with the results of residual stresses by the imaginary force method. The residual stress results that are determined by the finite element method are compared with the residual stress results that are calculated by the imaginary force method.